2020
DOI: 10.3390/antibiotics9070429
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic-Antiapoptotic Dual Function of Clinacanthus nutans (Burm. f.) Lindau Leaf Extracts against Bovine Mastitis

Abstract: Mastitis caused by bacterial infection has negative impacts on milk quality and animal health, and ultimately causes economic losses to the dairy industry worldwide. Gram-negative bacteria and their component lipopolysaccharide (LPS) can trigger the inflammatory response of endothelial cells (ECs) and subsequently promote EC dysfunction or injury, which is a critical pathogenesis of mastitis-causing sepsis shock. To control the bacterial infection and to minimise the LPS negative effects on ECs, we thus aimed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“…Clinacanthus nutans ethanolic extract was found to have anti-apoptotic effects against LPS-induced damage in bovine endothelial cells. This could be due to an effect of its components, glyceryl 1,3-disterate, kaempferol 3- O -feruloyl-sophoroside 7- O -glucoside, and hydroxypthioceranic acid, which showed pro-surviving Bcl-2 and pro-apoptotic Bax expression activities [ 30 ]. Clinacanthus nutans aqueous extracts could reduce LPS-induced increase in proinflammatory IL-1β expression but increase anti-inflammatory IL-2 and IL-4 expression in brain tissue after oral administration in rats [ 105 ].…”
Section: Clinacanthus Nutans Extracts On Inflammatory Pathwa...mentioning
confidence: 99%
“…Clinacanthus nutans ethanolic extract was found to have anti-apoptotic effects against LPS-induced damage in bovine endothelial cells. This could be due to an effect of its components, glyceryl 1,3-disterate, kaempferol 3- O -feruloyl-sophoroside 7- O -glucoside, and hydroxypthioceranic acid, which showed pro-surviving Bcl-2 and pro-apoptotic Bax expression activities [ 30 ]. Clinacanthus nutans aqueous extracts could reduce LPS-induced increase in proinflammatory IL-1β expression but increase anti-inflammatory IL-2 and IL-4 expression in brain tissue after oral administration in rats [ 105 ].…”
Section: Clinacanthus Nutans Extracts On Inflammatory Pathwa...mentioning
confidence: 99%
“…The parts of this plant mainly the leaves have been used traditionally to treat several virus infectious diseases and injuries, such as burns, skin rashes, and animal bites [ 2 , 4 ]. To date, the pharmacological activities of C. nutans have been reported, revealing the broad-range biological activities of C. nutans extract, which can be applied for therapeutic uses owing to its anti-virus [ 5 , 6 ], anti-inflammatory [ 7 ], anti-bacterial [ 8 , 9 ], anti-tumorigenic [ 10 ], and immunostimulating activities [ 7 , 10 ]. Unfortunately, only a few C. nutans products are commercially available currently and are mainly limited to the treatment of varicella-zoster and herpes simplex virus infections.…”
Section: Introductionmentioning
confidence: 99%
“…Since plant-based medicine naturally promotes synergistic effects, it represents high potential for supplying agents that can obviate multidrug resistance mechanisms. Recently, our research group reported the feasible activity of C. nutans extract in controlling bacterial growth in a bovine mastitis model [ 9 ]. Importantly, the treatment could effectively protect bovine endothelial cells from LPS-induced cell death [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mastitis is a common disease in dairy cows, causing inflammatory pathology in mammary tissue mainly induced by bacterial infection of the breast [1]. Bacteria invading breast tissue can not only lead to a decline in mammary gland function and blockage of the nipple ducts, but can also induce the production of a large amount of toxins and inflammatory factors that reside in the milk, which ultimately cause reduced yield and quality of milk [2] and occasionally lead to the death of dairy cows [3]. Worse still, milking can also cause chronic subclinical infections among cattle [4].…”
Section: Introductionmentioning
confidence: 99%